2022
DOI: 10.1002/ccr3.6671
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinally extensive transverse myelopathy in spinal cord infarction

Abstract: Spinal cord infarction may present as longitudinally extensive myelopathy, similar to inflammatory myelitis such as neuromyelitis optica. Magnetic resonance imaging features such as diffusion‐weighted imaging/apparent diffusion coefficient showing restricted diffusion and lack of contrast enhancement are helpful in the diagnosis of spinal cord infarction and differentiating them from inflammatory myelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Our aim is to comment on recent literature about challenging extensive SCIs (2) , (3) , (4) , (5) . Chiew YR, et al reported the case study of a 58-year-old male, who had the diagnosis of an extensive SCI established by the contrast-enhanced thoracic spine MRI diffusion-weighted imaging and apparent diffusion coefficient (DWI and ADC) evaluations (2) .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our aim is to comment on recent literature about challenging extensive SCIs (2) , (3) , (4) , (5) . Chiew YR, et al reported the case study of a 58-year-old male, who had the diagnosis of an extensive SCI established by the contrast-enhanced thoracic spine MRI diffusion-weighted imaging and apparent diffusion coefficient (DWI and ADC) evaluations (2) .…”
mentioning
confidence: 99%
“…Our aim is to comment on recent literature about challenging extensive SCIs (2) , (3) , (4) , (5) . Chiew YR, et al reported the case study of a 58-year-old male, who had the diagnosis of an extensive SCI established by the contrast-enhanced thoracic spine MRI diffusion-weighted imaging and apparent diffusion coefficient (DWI and ADC) evaluations (2) . The authors emphasized the differences between longitudinally extensive lesions of SCI and neuromyelitis optica (NMO); the lack of contrast enhancement in SCI is due to disrupted blood flow, and in NMO it occurs by inflammation and the intact blood flow (2) .…”
mentioning
confidence: 99%
See 1 more Smart Citation